DESAIN PROMOSI VISUAL JAMU “ASEREHE” BAGI DEWASA MUDA BERBASIS RISET: Jamu “Aserehe” Visual Promotion Design for Young Adults Based on Research - Edy Chandra; Mery Sevila (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Jamu “Aserehe” Visual Promotion Design for Young Adults Based on Research. This study designs a visual communication system to promote the herbal drink “Aserehe” to Indonesian young adults. Addressing a persistent gap between the perception of jamu as “old-fashioned/bitter” and the lifestyle demands of convenience and freshness, the research adopts a research-based design approach to directly link empirical insights to design decisions. Methods include exploratory interviews (brand owner and early users; n = 6), a descriptive survey (n = 80) to map taste perception, brand image, and trial intention, and a focused group discussion (FGD; n = [fill in]) to validate creative concepts. Findings are synthesized into the 4A+A strategy—Aware, Appeal, Ask, Act, and Advocate—and operationalized across integrated outputs: Instagram assets (feed, stories, reels), e-commerce posters, flyers, and vouchers, and an activation booth design. The visual system balances contemporary cues (clean typography, fresh palette, expressive illustration) with markers of traditional identity (heritage narrative and functional benefits). Implementation yields a replicable set of application guidelines that supports consistent cross-channel execution. The study contributes to small-business communication design by demonstrating how consumer perception data can be transformed into measurable design requirements. Future research should evaluate pre–post effects (awareness, trial intention, and digital engagement) and test live activations to verify the effectiveness and durability of the 4A+A-driven system.